Extrato etanólico da folha de Syzygium cumini L na alimentação de poedeiras leves - Silva, Valquíria Sousa (2023)
The objective of this study is to evaluate the ethanolic extract of the leaf of Syzygium cumini L in the diet of laying hens on the productive performance, quality of fresh and stored eggs, as well as lipid oxidation in the body of the birds. A total of 336 31-week-old Lohmann LS - Lite laying hens were used in a completely randomized design with seven treatments and six replications of eight birds. The treatments consisted of rations, being negative control (without addition of antioxidant), positive control (addition of 200 mg/kg of BHT antioxidant ration) and five rations with the inclusion of levels of ethanolic extract of the leaf of Syzygium cumini L of 200, 400, 600, 800, and 1000 mg/kg of feed. Productive performance, internal and external quality of eggs and lipid oxidation of blood serum, liver and segments of reproductive organs were evaluated. After 84 days of feeding, the eggs from these birds were evaluated fresh and stored for 28 days at room temperature in which the indicators of internal and external quality, total phenolics, capacity and antioxidant activity (DPPH and ABTS) in the eggs and the lipid oxidation (TBARS) in yolk. There was no significant effect on performance parameters, egg quality and lipid oxidation of blood, liver and reproductive organ segments. In the analysis of fresh and stored eggs, a decrease in the quality of eggs stored for 28 days was observed, and interaction between factors (rations and storage time) for total phenolics, where it was verified that the eggs of birds fed with the different rations showed a lower proportion of phenolics at 28 days, and the amount of phenolics in the eggs of birds fed the diet without additive or with BHT were lower in relation to birds fed with the levels of extract, both in fresh and stored eggs. For DPPH and ABTS in eggs, the values found in eggs from birds fed with diets without additive or with BHT were lower in relation to eggs from birds fed with different levels of extract. The TBARS values determined in the yolks of the birds fed with the diet without additive were higher in relation to BHT and the different levels of extract, since in the different levels of addition of the extract in the diet, there was difference only between the results with the dose of 1000 mg/kg in relation to doses of 600 and 800 mg/kg. There was also a quadratic effect of extract levels on TBARS values with a reduction in lipid oxidation up to the estimated level of 571.43 mg of extract/kg of feed. It is concluded that the inclusion of up to 1000 mg/kg of ethanolic extract from the leaf of Syzigium cumini L in the laying diet does not have an adverse effect on productive performance and egg quality, nor does it affect lipid oxidation in the body. However, it increases the amount of total phenolics, DPPH and ABTS in the eggs and reduces the lipid oxidation of the yolks in fresh eggs and eggs stored for 28 days, with the optimum level of inclusion estimated at 571.43 mg of extract/kg of feed.